Gradient structure of the cascade system - Takaessu Junior, Carlos Roberto (2021)
In this work we approach the theory necessary to solve one of the problems present in the article (ARAGÃO-COSTA et al., 2013), related to the cascade system. The present paper is divided in three parts: the first part is dedicated to study results and concepts from autonomous dynamical systems, such as the robustness of gradient semigroups, for example. The second part is dedicated to the concepts of non-autonomous dynamical systems like pullback attractors, exponential dichotomy and hyperbolic global solutions. The third part is the application, related to the cascade systems, of the first two chapters. Even though the cascade systems are autonomous, it benefits considerably from the theory of non-autonomous attractors, in particular of the skew-product formulation.